2021
DOI: 10.3389/feart.2021.645596
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Lithological Heterogeneity Within Opalinus Clay: Toward a Uniform Subfacies Classification Scheme Using a Novel Automated Core Image Recognition Tool

Abstract: The Opalinus Clay is notable in Switzerland as being the selected host rock for deep geological disposal of radioactive waste. Since the early 1990’s, this argillaceous mudstone formation of Jurassic age has been intensively studied within the framework of national and international projects to characterize its geological, hydrological, mechanical, thermal, chemical, and biological properties. While there is no formal stratigraphic subdivision, the Opalinus Clay lithology is classically divided into several, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
(138 reference statements)
0
7
0
Order By: Relevance
“…The shaly facies (Fig. 1b, d) is composed of rather homogeneous, dark-grey, laminated, argillaceous claystones mainly consisting of clay minerals (illite, illite-smectite kaolinite and chlorite) with silt to fine-sand sized bioclasts (e.g., fossil shells) and detrital quartz and feldspar grains dispersed throughout the clay-rich matrix (Kneuker and Furche 2021;Lauper et al 2021). The OPA sandy facies (Fig.…”
Section: Sample Characterization and Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The shaly facies (Fig. 1b, d) is composed of rather homogeneous, dark-grey, laminated, argillaceous claystones mainly consisting of clay minerals (illite, illite-smectite kaolinite and chlorite) with silt to fine-sand sized bioclasts (e.g., fossil shells) and detrital quartz and feldspar grains dispersed throughout the clay-rich matrix (Kneuker and Furche 2021;Lauper et al 2021). The OPA sandy facies (Fig.…”
Section: Sample Characterization and Preparationmentioning
confidence: 99%
“…The OPA sandy facies (Fig. 1a, c) is a heterogeneous, siliceous-argillaceous claystone, characterized by an alternation of dark-grey, clay-rich layers and undulating lenses and layers of silt to sand-sized quartz and feldspar grains, cemented by carbonates (Lauper et al 2018(Lauper et al , 2021Schuster et al 2021). Well-pronounced bedding planes of OPA are caused by the preferential alignment of phyllosilicates, leading to a transverse isotropy of petrophysical, mechanical and hydraulic properties (e.g., NAGRA 2002;Wenk et al 2008;Siegesmund et al 2014;Favero et al 2018;Schuster et al 2021).…”
Section: Sample Characterization and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, it consists of 60 ± 12 wt% clay minerals (illite, illite/smectite mixed layers, kaolinite, chlorite), 22 ± 6 wt% quartz and feldspars, 13 ± 10 wt % calcite and minor contributions of siderite, pyrite and organic matter (Mazurek, 2011). In the vertical dimension, lithological sub-units, reflecting slight variations in sedimentary facies, were defined by Lauper et al (2021). Owing to maximum burial in the Cretaceous and subsequent basin inversion (Mazurek et al, 2006;Giger et al, 2015), the Opalinus Clay is an indurated and over-consolidated shale.…”
Section: Geological Settingmentioning
confidence: 99%
“…Such heterogeneities are responsible for the observed heterogeneous diffusion patterns at the core scale (Bollermann et al, 2022). At the core scale, Lauper et al (2021) quantified the lithological heterogeneity within OPA from northern Switzerland. They concluded that most of the investigated OPA can be described by five distinctive subfacies types that are visually and quantitatively distinguishable by texture and composition.…”
Section: Introductionmentioning
confidence: 99%